FACTORS INFLUENCING ARABLE CROP FARMERS’ WILLINGNESS TO COLLABORATE WITH INVESTORS IN KWARA STATE, NIGERIA - Olabanji, O.P.; Dolapo, T.A.; Rahmat Ayodele; Oduntan, R.A.; Bonire, J.O. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the factors influencing arable farmers’ willingness to collaborate with investors in Kwara State, Nigeria. A multistage sampling procedure was used to select 150 arable farmers. Data were collected through a structured interview schedule and analyzed using descriptive statistics and binary logistic regression. Results revealed that majority (84.7%) of the respondents were male, with a mean age and farming experience of 52.7 years and 28.3 years, respectively. Also, majority (85.3%) expressed willingness to collaborate, awareness of available collaboration opportunities was generally low (WMS = 0.76). Off-taker (WMS = 1.25) and proxy-farming arrangements (WMS = 1.23) were the most familiar partnership models. Farmers exhibited positive perceptions of collaboration with investors. The logistic regression model (χ² = 56.874, p < 0.001; Nagelkerke R² = 0.547) showed that sex, age, marital status, educational attainment, farm ownership, farm size, farming experience, awareness, and perception significantly influenced willingness to collaborate (p < 0.05). Major constraints identified included poor awareness of collaboration opportunities (x =2.29), production risks (x = 2.18), market uncertainty (x = 2.09), and limited extension services (x = 1.76). The study concludes that sex, age, marital status, educational attainment, farm ownership, farm size, farming experience, awareness, and perception were the factors influencing arable farmers’ willingness to collaborate with investors in the study area. It is recommended that targeted awareness campaigns, inclusive investment models, and strengthened extension systems be implemented to promote mutually beneficial collaborations that enhance agricultural productivity and sustainability.